2018
DOI: 10.3989/scimar.04764.18a
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mesh size and shape on the size selection of European hake (<em>Merluccius merluccius</em>) in demersal trawl codends: An investigation based on fish morphology and simulation of mesh geometry

Abstract: European hake (Merluccius merluccius) is an important commercial species for several European bottom trawl fisheries. Therefore, understanding the influence of codend mesh size and shape on the size selection of European hake is critical for defining technical measures for fisheries targeting this species. Based on morphology data collected on European hake, the influence of mesh size and shape on bottom trawl codend size selectivity was investigated by simulation using the FISHSELECT methodology successfully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The effect of a gap would be most noticeable for fish species that, like Nephrops, position themselves close to the lower panel of the gear (Graham and Fryer, 2006;Melli et al, 2019). Relative to the moving trawl, hake reportedly drift backwards close to the lower panel (Alzorriz et al, 2016;Cuende et al, 2020), and the results from cruises 1 and 2 showed that the catch increase in the trawls with the lower gap in the grid became significant for hake of approximately 15 cm, which is probably the size at which they begin to have difficulty passing through the 19 mm bar spacing of the grid (Tokaç et al, 2018). A similar pattern was observed in the catch comparison results for both velvet belly and spiny dogfish.…”
Section: Discussionmentioning
confidence: 95%
“…The effect of a gap would be most noticeable for fish species that, like Nephrops, position themselves close to the lower panel of the gear (Graham and Fryer, 2006;Melli et al, 2019). Relative to the moving trawl, hake reportedly drift backwards close to the lower panel (Alzorriz et al, 2016;Cuende et al, 2020), and the results from cruises 1 and 2 showed that the catch increase in the trawls with the lower gap in the grid became significant for hake of approximately 15 cm, which is probably the size at which they begin to have difficulty passing through the 19 mm bar spacing of the grid (Tokaç et al, 2018). A similar pattern was observed in the catch comparison results for both velvet belly and spiny dogfish.…”
Section: Discussionmentioning
confidence: 95%
“…From related sorting grid and square mesh selectivity studies (e.g. [ 23 , 24 ]) and the fall-through experiment of this study, it was hypothesized that the length-based rejection rate of the 70mm square meshes of the Excluder would be substantially higher (round fish L50 of approx. 25 cm) than for the 35mm bar distance of the grid (round fish L50 of approx.…”
Section: Discussionmentioning
confidence: 99%
“…Since diamond mesh codends are typically more selective for flatfish than for roundfish species [ 48 – 50 ] a square mesh codend design (CD S ) was also considered ( Fig 1 ). The design guides made by Tokaç et al [ 51 ] showed that a 60 mm mesh size with an opening angle of 90° would result on a L 50 of approximately 25 cm for hake. However, in order to get a compromise between releasing undersized hake and not losing other important species for the fishery, the CD S tested in this study was 7.0 m long, double-braided 3.5 mm polyethylene, forming 63.20 ± 1.73 mm (mean ± SD) meshes.…”
Section: Methodsmentioning
confidence: 99%
“…A flaw in the experimental design resulted in obvious differences in the mesh sizes used for SMP BS and SMP BL PC s and CD D and CD S CC s. Given that, we could not rule out that some of the smallest hake and blue whiting individuals might escape through the cover meshes. According to predictions made by Tokaç et al [ 51 ], a 40 mm diamond mesh would be able to release hake between approximately 8 and 17 cm depending on mesh opening angle. Similarly, and based on the predictions for blue whiting in Cuende et al [ 62 ], the same mesh size and mesh opening angles would release individuals ranging between 8 and 20 cm.…”
Section: Methodsmentioning
confidence: 99%